Spiritual Coping Approach in Islamic Education to Reduce Students' Academic and Personal Stress - Nurfadilah, Utami; Rahmat, Munawar; Surahman, Cucu (International Journal of Islamic Studies Higher Education, 2025)
Academic pressure, future uncertainty, and social challenges often trigger prolonged stress among students. This study examines the role of spiritual coping, grounded in Islamic educational values, in managing both academic and personal stress. Using a qualitative case study method, data were collected from twelve students selected through purposive sampling. These students were experiencing stress but actively practiced spiritual coping strategies, such as prayer, reflection on Islamic teachings, and participation in religious communities. Data were gathered through in-depth interviews, observations, and documentation, and analyzed using the Miles and Huberman interactive model, which includes data reduction, display, and conclusion drawing. Findings reveal that spiritual practices such as the remembrance of God, Quranic recitation, patience, gratitude, and sincerity contribute significantly to emotional stability and stress reduction. These coping mechanisms enhance inner peace and resilience, while involvement in campus religious environments fosters a sense of spiritual and social belonging. The study concludes that spiritual coping in the context of Islamic education is not merely an emotional response but a transformative strategy that reinforces psychological resilience. The findings suggest practical implications for student support services, curriculum development, and the role of educators in nurturing students’ emotional and spiritual well-being.